2015
DOI: 10.1016/j.apjtb.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora crispa extract inhibits MMP-13 and migration of head and neck squamous cell carcinoma cell lines

Abstract: A B S T R A C TObjective: To investigate the effect of Tinospora crispa (T. crispa) extract on matrix metalloproteinase-13 (MMP-13) expression and cell migration. Methods: The cytotoxicity of T. crispa extract was examined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay on head and neck squamous cell carcinoma (HNSCC) cell lines. The effect on expression of MMP-13 was analysed by RT-PCR and ELISA. The migration was assessed by wound healing assay. Results: MMP-13 mRNA was highly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Furthermore, cells were maintained in normal growth medium with or without DAPT supplementation for 24 h. At 0 and 24 h, images of the wound were captured at the same location using mark on phase contrast microscope to directly compare gap of the wound. Relative migration ratio was calculated based on previous study (38).…”
Section: Wound Healing Assaymentioning
confidence: 99%
“…Furthermore, cells were maintained in normal growth medium with or without DAPT supplementation for 24 h. At 0 and 24 h, images of the wound were captured at the same location using mark on phase contrast microscope to directly compare gap of the wound. Relative migration ratio was calculated based on previous study (38).…”
Section: Wound Healing Assaymentioning
confidence: 99%
“…Here we observed a high MMP-13 expression in MIA induced hADMSCs in comparison to DM preconditioned hADMSCs ( Figure 5e ). Prior studies conducted also indicates downregulation of MMP-13 has been reported in human HNSCC, HN22, HSC-3 and RAW 264.7 cell lines using Tinospora crispa and Morus alba plant extracts [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, T. crispa stem extracts were able to reduce the cell viability of K562 cells with different incubation period. From the previous study, it was found that T. crispa stem extract reduced the cell viability of different panel of cell lines such as MCF-7, HeLa, HN22 and HSC with the highest concentration of 100 µg/mL for MCF-7 and HeLa (Ibahim et al, 2011;Phienwej et al, 2015). These studies emphasized the potential of T. crispa stem extracts have potential cytotoxic effect on K562 cell but not reducing until 50% of the cell viability.…”
Section: Aqueous Extractmentioning
confidence: 95%